Household carbon dioxide emissions in the United States: the role of demographic change - Underwood, Anthony J., author; Kling, Robert, advisor; Zahran, Sammy, advisor; Iverson, Terrence, committee member; Costanigro, Marco, committee member (Colorado State University. Libraries, 2013)
This dissertation is comprised of five chapters discussing the importance of the measurement of household carbon dioxide emissions and the demographic determinants of those emissions in developing an understanding of anthropogenic climate change and the potential for future carbon dioxide emissions mitigation strategies. Chapter 1 discusses the scientific consensus regarding the impact of human activities in generating global warming and the effects of this warming on the earth's climate. In Chapter 2, I first discuss the Consumer Expenditure Survey data compiled and the methodology used to measure household carbon intensity of expenditures and carbon dioxide emissions, combining economic input-output modeling with a life cycle assessment modeling to track industry to industry transactions and the corresponding resource use from extraction to end use disposal. Second, I show that carbon pricing policies are indeed regressive with lower income households having significantly higher carbon intensities of consumption. As suggested in the previous literature, this result stems from the allocation of household expenditures among direct and indirect uses of energy. This expenditure allocation decision is driven, not only by household income, but also by characteristics that vary over the life course, most notably household size and composition. Therefore, lastly I show that household carbon dioxide emissions and intensities follow distinct trajectories over the life cycle, independent of household income, resulting from a reallocation of expenditures necessitated by the evolving needs of households at different stages in the life cycle. In Chapter 3, I discuss the demographic characteristics that are the drivers of the variation in emissions and intensities among heterogeneous households and how these demographic characteristics have changed, on average, over the past few decades in the United States. Of these changes, most notable are changes in mean household size, the age of household head, and the proportion of one- and two-person households. As baby boomers begin to retire and young individuals choose delay or forego household formation, expenditure allocation decisions of the average household are evolving, thereby changing the relationship between population growth and carbon dioxide emissions in the United States. In Chapter 4, to formalize the channel through which these changing dynamics of population growth and CO2 emissions occur, I first generate age-emissions profiles to show the importance of the age of a household member in contributing to total household emissions. I find that children contribute dramatically less than an adult and elderly contribute relatively less than an adult, but more than a child; results which are consistent with findings in the previous literature. In other words, an individual follows a distinct trajectory of emissions over their lifetime. The magnitude of this emissions curve is being attenuated over time as a result of improvements in energy efficiency, but these reductions are becoming smaller in time, consistent with the concept of diminishing returns to technology. Second, to incorporate the ability of households to experience economies of scale in their emissions through cohabitation, I construct an equivalence scale model in which I adjust for both the size and composition of households in the estimation of household CO2 emissions. I find that the ability of the average household in the United States to experience economies of scale in emissions has decreased since 2003 resulting in a substantial increase in mean household emissions. Lastly, to quantify this effect I use counter-factual prediction to determine that mean household carbon dioxide emissions would be over ten percent lower in 2009 if the ability of households to experience economies of scale had remained constant at 2003 levels. Finally, in Chapter 5 I highlight the importance and policy implications of this research, most importantly regarding the consideration of the composition of the population when estimating and projecting greenhouse gas emissions. Given the differences in energy use and emissions among households of different sizes and compositions, if the proportions of these population groups change over the next century in the developing world, as they have in developed nations over the past century, then emissions projections using population growth and estimates of per capita emissions may result in misleading conclusions regarding mitigation strategies and adaptation policies in a changing global climate.
Keywords: carbon dioxide emissions; climate change; demographic change; economies of scale; household expenditures